Günümüzde papalık teşkilatı - Işık, Halim (My University, 2001)
Hristiyanlık bünyesinden çıkmış olan Katolik mezhebi, hiyerarşik yapısını oluşturan Papalık Teşkilâtı ile din- siyâset tarihinde çok önemli bir yer tutmaktadır. Papalık, bu makamı , İsa'nın , İncillerdeki Sen Petrus'sun ve ben kilisemi bu kayanın üzerine kuracağım örneğindeki ifadelerinin muhatabı ve birinci papa kabul ettiği Havâri Petrus'un halefi ve İsa Mesih'in vekili konumunda görür. İki bin yıllık tarihinin başlangıcına koyduğu bu Havâri ile başlayan papalık teşkilâtı , üç yüzden fazla papayı iktidara getirmiş, asırlar boyunca birçok kaos dönemi geçirmiş, en etkin dönemini Ortaçağda yaşamış, Haçlı seferleri' nin faillerinden olmuştur. Havâri Petrus sonrası, çok şâibeli seçim dönemleri akabinde papalık seçimleri evrim geçirmiş, nihayet görevi müstakbel papayı seçmek olan Kardinaller Meclisi oluşturularak sistematik yapıya kavuşturulmuştur. Sembol bir bayrak, marş, para birimi, güvenlik sistemi ile devlet olması 1929'da Papa XI. Pie ve Mussolini' nin imzaladığı Latran Antlaşmaları sonucu gerçekleşen Vatikan, adını Havâri Petrus'un şehid edildiği ve keramet göstermek anlamında, Roma'daki Vaticanus tepelerinden almaktadır. 44 hektar ile dünyanın en küçük yüzölçümüne sahip, katolik dünyasının merkezi bu mikro devlet , dünya tarihinde örneği olmayan bir karakter arz eder. Bağlı birçok ilâhiyat fakültesi, enstitü , akademi, lise ve araştırma kurumları ile Vatikan dünya çapında organize meclislere, televizyon-radyo merkezleri ve her türlü medya organlarına sahiptir. Diğer kiliseler ve dinlerle münasebetlerinde ılımlı fakat tavizsiz bir karakterde olan papalık, bilhassa Yahudilik ile tarihinin en sıcak ilişkileri içindedir. Günümüzdeki iktidarını asıl adı Karol Joseph Wojtyla olan Papa II. Jean-Paul' ün 20 yılı aşkın süredir yürüttüğü papalık, yakın bir dönemde yeni bir papa seçimi yaşayacaktır. İktidara geldiğinde modern, ilerleyen dönemlerde muhafazakâr portre çizen Polonya asıllı II. Jean- Paul, komünist bir ülke mensubu, dünyanın her tarafına ulaşan seyahat ve mesajları, 455 yıldan bu yana İtalyan asıllı olmayan ilk papa olmak gibi özellikleri ile temâyüz etmektedir.

PAPACY ORGANIZATION IN OUR TIME Catholic Sect which comes from Christianity has a very important place between Papacy Organization taking form from the structure of Catholic hierarchy and history of religion and politics. Papacy sees this organization as the collator of Jesus, St. Petrus and the expression I'm going to build my church on this rock. Also Papacy sees it as the representative of Christ and the descendant of Disciple Petrus who is admitted as the first pope. Papacy Organization which started with this Disciple at the beginning of 2000-year-history of Papacy has brought more than three hundred popes to power. It has had a lot of chaotic times for centuries. It lived its most effective time in Medieval Age and was one of the subjects of the Crusaders. After the Disciple Petrus, the Pope Elections had been developed following the election terms and brought more than three hundred popes to the power, and finally it had a systematic structure founding Council of Cardinals whose duty is to elect the future pope. Vatican became true government with its flag , currency , march and safety system with Latin Agreement , which was signed between Pope XI Pie and Mussolini. It takes its name from the Vaticanus Hills in Rome where Disciple Petrus was killed and of which meaning is to work miracle. This micro government which is the center of Catholic world has the smallest area of the world with 44 hectares and has unique character which hasn't been in the history of world. Vatican with a lot of related faculties of theology, institutes, academies , high schools and searching institutions has got the most organized councils, television-radio centers and every kind of most developed media agencies. The papacy is administrated by II Jean Paul, whose real name Karol Joseph Wojtyla is, is managed for more than 20 years and will live an election for a new pope in the near future. II Jean Paul whose real origin is Pole seemed modern when he came to power and in the following times he seemed conservative. He is the member of a communist country .His travellings and messages reaching all over the world and his being the first pope whose real origin is not Italian first after 455 years are his specialities and unique features.
Keywords: Dinler; Hıristiyanlık Felsefe; Papalık